Design and Simulation Optimization of the Double Cam Clamping Mechanism in Marking Production Line - Li Xiaoqian; Ren Xiuhua; Zhang Chao; Pan Shouguang; Wang Rijun; Chen Qingkui (Jixie chuandong)
In order to better meet the work requirements of the marking production line to remove the unqualified workpieces, this study designs a double cam clamping mechanism which can realize the clamping and lifting of the workpieces with only one power source. The motion sequence of two cams is designed based on the action sequence of clamping and removing the unqualified workpieces. The contour curve of the cams is calculated by Matlab software, and the 3D model is built on SolidWorks platform. Adams software is used to complete the parametric modeling and motion simulation of the double-cam clamping mechanism. The results show that the output motion law of the mechanism is consistent with the designed motion law. Through the optimization design of the key coordinate position, the appropriate position parameters of the key coordinate are obtained. The double-cam clamping mechanism can effectively save cost and improve work efficiency, and has certain theoretical value and high application value for practical production line.